Combat "Category A" Calls: Evaluating The Prehospital Timelines in a Military Trauma System. Issue 4 (1st December 2007) - McLeod, J; Hodgetts, T; Mahoney, P
Abstract : Aim: To establish the pre-hospital timelines for seriously injured UK military casualties on OP HERRICK. Population: All consecutive MERT and MERT-E mobilizations from Camp Bastion, Helmand Province, between 04 May 06 and 18 Jun 07. Methods: Interrogation of MS Access database compiled from paper patient report forms for each casualty transported. Results: 528 patients were transported. 84.6% (456) were battle casualties. There were 192 GSW and 233 casualties with blast/fragmentation injuries. 189 of 528 (35.7%) were UK Service personnel. Median time from injury to handover at the emergency department for UK military T1 casualty subset was 99 minutes. Conclusion: The public perception of excessive timelines for pre-hospital care in Afghanistan has been distorted. The ground truth is a pre-hospital time less than one quarter of the cited 7 hours for the seriously injured subset of UK Service personnel.